ANALISIS ADMINISTRASI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMK NEGERI 1 TATAPAAN - Tombokan, Shinta Novralia; Mamentu, Meike (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2024)
This research discusses the analysis of teacher administration in improving the quality of learning at SMK Negeri 1 Tatapaan. Where teacher administration is a key factor in improving the quality of learning. Through the descriptive method with qualitative data types, data collection techniques are carried out by means of observation, interviews and documentation. Data analysis methods are carried out starting from data collection, data reduction, data analysis and drawing conclusions. This research explores teacher administrative practices that impact the quality of learning. Results of research at SMK Negeri 1 Tatapaan. States that teacher administration is very necessary in improving the quality of learning. Where this concerns the readiness and ability of teachers in the success of the learning process in keeping up with current developments, especially in improving the quality of learning in schools.